Hepatic organic anion transporting polypeptides mediate disposition of milk thistle flavonolignans and pharmacokinetic silymarin‐drug interactions. (15th February 2021) - Lynch, Katherine D.; Montonye, Michelle L.; Tian, Dan‐Dan; Arman, Tarana; Oyanna, Victoria O.; Bechtold, Baron J.; Graf, Tyler N.; Oberlies, Nicholas H.; Paine, Mary F.; Clarke, John D.
Abstract : Silybum marianum (L.) Gaertn. (Asteraceae), commonly known as milk thistle, is a botanical natural product used to self‐treat multiple diseases such as Type 2 diabetes mellitus and nonalcoholic steatohepatitis (NASH). An extract from milk thistle seeds (achenes), termed silymarin, is comprised primarily of several flavonolignans. Systemic concentrations of these flavonolignans can influence the potential biologic effects of silymarin and the risk for pharmacokinetic silymarin‐drug interactions. The aims of this research were to determine the roles of organic anion transporting polypeptides (OATPs/Oatps) in silymarin flavonolignan disposition and in pharmacokinetic silymarin‐drug interactions. The seven major flavonolignans from silymarin were determined to be substrates for OATP1B1, OATP1B3, and OATP2B1. Sprague Dawley rats were fed either a control diet or a NASH‐inducing diet and administered pitavastatin (OATP/Oatp probe substrate), followed by silymarin via oral gavage. Decreased protein expression of Oatp1b2 and Oatp1a4 in NASH animals increased flavonolignan area under the plasma concentration‐time curve (AUC) and maximum plasma concentration. The combination of silymarin inhibition of Oatps and NASH‐associated decrease in Oatp expression caused an additive increase in plasma pitavastatin AUC in the animals. These data indicate that OATPs/Oatps contribute to flavonolignan cellular uptake and mediate the interaction between silymarin and NASH on pitavastatin systemic exposure.